Pengaruh Currency Dan Co-Creation Terhadap Customer Loyalty Yang Dimediasi Oleh Customer Satisfaction - Milinia, Wanda; Bintarti, Surya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Modern lifestyle includes daily human habits that are in accordance with the demands of the times. Instant noodles have become an alternative food for the majority of the Indonesian population. PT Lemonilo Indonesia Sehat is a startup company based in West Jakarta. Lemonilo was founded by Shinta Nurfauzia (CEO and Founder), Ronald Wijaya (Co-CEO), and Johannes Ardiant (Chief Product & Technology) in 2015. On October 1, 2016, Lemonilo officially started with the concept of a healthy lifestyle. This is related to the observations of the founders regarding the availability of healthy food in the market at high prices. In addition to e-commerce, Lemonilo products can be purchased through a mobile application and in some supermarket and minimarket areas. Lemonilo is also present in 28 regions in Indonesia. The purpose of this research is to test the influence of currency and co-creation on customer loyalty mediated by customer satisfaction in healthy lemonilo instant noodles. This research was conducted within the boundaries of the Bekasi district community area with a sample of 107 respondents. The technique for taking respondents that uses a non-probability sampling population is purposive sampling. This research tests correlation and regression with the help of SmartPLS 3.2.9 which is used to test validity and reliability. The study indicates that the reliability test results using Cronbach’s Alpha or Composite Reliability show a value of 0.7, concluding that the tested variables are valid, allowing the continuation of structural model testing and potential further development into a thesis.